SAVE: Steps in Achieving Viable Energy—Teacher Edition - Nathan Mitten; H.A. (Skip) Ingley; Jessica Kochert; Joy C. Jordan (EDIS)
The 4-H SAVE project is an energy education curriculum that targets youth, ages 11 to 13. The project takes youth on a journey through the exciting world of energy.